2021
DOI: 10.1073/pnas.2114156118
|View full text |Cite
|
Sign up to set email alerts
|

Stable lariats bearing a snoRNA (slb-snoRNA) in eukaryotic cells: A level of regulation for guide RNAs

Abstract: Small nucleolar (sno)RNAs guide posttranscriptional modifications essential for the biogenesis and function of their target. The majority of snoRNAs in higher eukaryotes are encoded within introns. They are first released from nascent transcripts in the form of a lariat and rapidly targeted by the debranching enzyme and nuclear exonucleases for linearization and further trimming. In this study, we report that some snoRNAs are encoded within unusually stable intronic RNAs. These intronic sequences can escape th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Furthermore, the presence of dyskerin in the cytoplasm was also confirmed by immunofluorescence microscopy. This finding is also in line with what has been recently reported for a sub-class of H/ACA snoRNA-bearing transcripts encoded as stable lariats that can be found in the cytoplasm associated with ectopically expressed snoRNA binding proteins such as dyskerin and GAR1 as we observed [42]. Although dyskerin is well-known to be localized in the nucleus, a previous study identified a cytoplasmic isoform of this protein characterized by a lower molecular weight [43].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the presence of dyskerin in the cytoplasm was also confirmed by immunofluorescence microscopy. This finding is also in line with what has been recently reported for a sub-class of H/ACA snoRNA-bearing transcripts encoded as stable lariats that can be found in the cytoplasm associated with ectopically expressed snoRNA binding proteins such as dyskerin and GAR1 as we observed [42]. Although dyskerin is well-known to be localized in the nucleus, a previous study identified a cytoplasmic isoform of this protein characterized by a lower molecular weight [43].…”
Section: Discussionsupporting
confidence: 93%
“…S2, S3). Besides, scMTD identified some novel molecular function terms related to the differentiation function [ 33 35 ]. Furthermore, we presented the expression distributions of the marker genes participating in each stage of differentiation in the raw data and scMTD imputed data, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, longer RNase R resistant stable intronic lariat bearing U85 scaRNA is observed in the nucleus (Figure S11 g). Another example of an RNase R resistant, stable intronic lariat bearing snoRNA in the oocyte nucleus is for the HSPA8 intron-encoded SNORD14 (Figure S11 f), previously described in chicken DF1 cells (Talross et al 2021). Such stable intronic lariats bearing snoRNA do not function as guide RNAs for rRNA and snRNA modification in contrast to mature snoRNA (Talross et al 2021).…”
Section: Chicken Oocyte Small Rnas Reflect Differential Cytoplasmic A...mentioning
confidence: 86%